Perwatakan dan Nilai Moral Tokoh Utama dalam Kumpulan Dongeng Ludwig Bechstein - Milasari Asiska; Misnah Mannahali (Phonologie : Journal of Language and Literature, 2022)
Abstract. This research purpose the value of character building in the drama Nathan der Weise, and its  relevance to German lessons at SMA.  The data analysus technique used is content analysis. This analysis technique consists of there stages.  They are data reduction, data display and conclusion. Based  on the result obtained from the Fed analysis that there are six values in the Drama Nathan der Weise that are relevant to the value of character building snd the German lesson Kurikulum 2013 at SMA. The six values are wisdom, tolerance, self-confidance, humalitiy, mutual help, and friendship. The relevance of these six values to German lessons using the role-playing method.Keywords: Nathan der Weise, Character buiding, Kurikulum 2013, Role-playing, Conten-Analysis.